Interpreting Estrogen Screening Assays in the Context of Potency and Human Exposure Relative to Natural Exposures to Phytoestrogens. (3rd January 2014) - Becker, Richard A.; Hays, Sean M.; Kirman, Christopher R.; Aylward, Lesa L.; Wise, Kimberly; Marty, M. Sue
<x xml:space="preserve">Abstract</x> While the Environmental Protection Agency and the Organization for Economic Cooperation and Development have developed validated in vitro and in vivo screening assays to measure interaction of substances with estrogen, androgen and thyroid pathway components, to date, methods to contextualize such results in terms of potencies and actual human exposures are lacking. To place endocrine screening results in the context of potency and human exposure, we propose a method that entails (1) calculating a benchmark dose for a response measured in an endocrine screen; (2) estimating the human urinary concentration (biomonitoring equivalent, BE) expected to correspond to this dose (BEBMD); (3) deriving the exposure:activity ratio (EAR) by comparing actual urinary values from human biomonitoring studies (e.g., National Health and Nutrition Examination Survey (NHANES)) to the BEBMD. Using OECD uterotrophic assay validation studies and NHANES results, we calculated EARs for genistein (EARGEN = 6.6 × 10−4) and bisphenol A (EARBPA = 8.8 × 10−7). The EARGEN is more than 700‐fold greater than the EARBPA. Not only can these methods be applied to additional endocrine assays and compounds, they can contribute to weight of evidence decisions regarding the need for additional endocrine screening and testing—substances with low EARs may not warrant additional testing.